Review Artikel: Analisis Tingkat Pengetahuan Resistensi Antibiotika dalam Kalangan Masyarakat - Klaritya Anisya Kurnia; Indah Laily Hilmi; Salman Salman (Journal of Pharmaceutical and Sciences, 2023)
Background: Antibiotics are needed to treat infections caused by pathogenic bacteria. The use of antibiotics to treat bacterial infections when carried out in an inappropriate manner can have adverse consequences both clinically and economically. Inappropriate dosage, timing and frequency of use can lead to resistance. From various studies in various places, it was found that the knowledge and behavior of the community in the use of antibiotics were still not wise and rational. One of the health problems is antibiotic resistance where many Indonesian people still do not understand antibiotic resistance, one of which is influenced by the behavior of using antibiotics. Several factors have been known to influence use including poor governance, weak enforcement of laws and lack of knowledge. Conclusion: of this activity is to know the level of society regarding antibiotics as well as antibiotic resistance. Methods: used is a literature review which was analyzed from several scientific publications in national journals regarding antibiotic resistance.